2019
DOI: 10.1186/s12891-019-2959-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic viscoelastic characterisation of human osteochondral tissue: understanding the effect of the cartilage-bone interface

Abstract: BackgroundDespite it being known that subchondral bone affects the viscoelasticity of cartilage, there has been little research into the mechanical properties of osteochondral tissue as a whole system. This study aims to unearth new knowledge concerning the dynamic behaviour of human subchondral bone and how energy is transferred through the cartilage-bone interface.MethodsDynamic mechanical analysis was used to determine the frequency-dependent (1–90 Hz) viscoelastic properties of the osteochondral unit (cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
(85 reference statements)
0
21
0
Order By: Relevance
“…An exponential increment profile of tissue stiffness at the interface was validated by FEA results to facilitate efficient force transfer and reduce stress concentrations to avoid tissue failure. The excellent force transfer properties of the interface tissue may be ascribed to the energy absorption and dissipation mechanism of the specific structures and compositions. ,, The nanoscale heterogeneity of HAp may facilitate force transfer by energy dissipation at the interface . The soft biomolecules like titin at the interface were crucial in dissipating energy through large deformation and viscoelastic properties. , These soft biomolecules also have extraordinary energy-absorbing capabilities via local deformation to favor force transfer of the interface tissues .…”
mentioning
confidence: 99%
“…An exponential increment profile of tissue stiffness at the interface was validated by FEA results to facilitate efficient force transfer and reduce stress concentrations to avoid tissue failure. The excellent force transfer properties of the interface tissue may be ascribed to the energy absorption and dissipation mechanism of the specific structures and compositions. ,, The nanoscale heterogeneity of HAp may facilitate force transfer by energy dissipation at the interface . The soft biomolecules like titin at the interface were crucial in dissipating energy through large deformation and viscoelastic properties. , These soft biomolecules also have extraordinary energy-absorbing capabilities via local deformation to favor force transfer of the interface tissues .…”
mentioning
confidence: 99%
“…This behavioral pattern of the same-application materials and the differences between the two types is consistent with the stress-relaxation properties of OC tissues. 84,85 The viscoelastic properties of a biomimetic material should match those of the replaced tissue to avoid the accumulation of residual stress, either in the implant or in the adjacent tissue, and do not compromise the successful restoration of the damaged site. Wang et al 86 found that an agarose gel grafted into an OC defect recovered faster than the neighboring cartilage after removing the applied load, causing a build-up of residual stress at the implant-tissue interface.…”
Section: Resultsmentioning
confidence: 99%
“…This behavioral pattern of the same-application materials and the differences between the two types is consistent with the stressrelaxation properties of OC tissues. 84,85 The viscoelastic properties of a biomimetic material should match those of the replaced tissue to avoid the accumulation of residual stress, either in the implant or in the adjacent tissue, and do not compromise the successful restoration of the damaged site.…”
Section: Papermentioning
confidence: 99%
“…Cartilage exhibits frequency-dependent viscoelastic behaviour [15,16]. Viscoelasticity can be characterised through a storage and loss modulus [17][18][19], or via storage and loss stiffness for a structure [20,21].…”
Section: Introductionmentioning
confidence: 99%